AN ANALYSIS OF STEREOTYPE IN ZOOTOPIA MOVIE - Atillah, Widya; Arifin, M. Bahri; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2020)
Stereotypes are preconceptions about individuals of group. Stereotypes are the common phenomena that happen in the daily activities of language use where sometimes people do not realize that they are stereotyping others. It is caused by a diversity of issues among the society. People tend to build some general perspectives that include the positive and negative things about a group of people. As a reflection of the real life, movies can also contain the phenomenon of stereotype such as in Zootopia movie. This research is aimed to describe the categories of stereotype and also to analyze the function of stereotype that were performed by several characters in Zootopia movie. This research was conducted by using descriptive method and qualitative approach. Data were taken from movie script in the form of utterances. The results of this research show that there are forty three data which are indicated as stereotyping utterances from eleven characters in Zootopia movie. In addition, the researchers identified six out of eight stereotype categories that have been used in this movie, namely Gender, Race, Physical Features, Occupation and Socioeconomic Status, National Groups and Other Category. Moreover, the researchers identified two stereotype functions in the movie, they are individual function and social or collective function.